Pengaruh Kompensasi dan Kompleksitas Tugas terhadap Kepuasan Kerja dengan Motivasi Kerja sebagai Variabel Intervening pada PT. Bank Sumut Cabang Sukaramai Medan - Julia Raisa Putri; Saskia Yusuf; Sunaryo Sunaryo (Target : Jurnal Manajemen Bisnis, 2021)
This study aims to determine the effect of compensation and task complexity on job satisfaction through work motivation directly or indirectly at PT. Bank Sumut Branch of Sukaramai Medan. Path analysis research design is used as an analytical tool to determine the direction of the variables studied and to justify how significant the influence of the dependent independent variable is directly and indirectly through the mediating variable. In this study, the associative method is used with a quantitative approach. In this study, the entire population that became the sample was 103 employees at PT. Bank Sumut, Sukaramai Branch Medan. The results showed that compensation had a significant effect on work motivation, task complexity had no and no significant effect on work motivation, compensation had a significant effect on job satisfaction, complexity. Duties have no and insignificant effect on job satisfaction, work motivation has a significant effect on job satisfaction, compensation has no significant effect on work motivation through job satisfaction, task complexity has no effect on job motivation through job satisfaction.